Penentuan Mitra Pemasok Produk Furnitur Menggunakan Metode AHP - Chandra, Annisa Ayudhita; Supangkat, Hendrarto Kurniawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Multiline Design has a new business line that operates in the field of ready stock furniture. Due to limited resources in making furniture, such as the absence of in-house craftsmen and raw materials, Multiline Design will only focus on the design function of the products being marketed. Companies need to work with external partners to supply raw materials and make products according to design. The main issue currently faced is how to determine the right supplier partner. This research aims to determine the sole supplier partner for furniture products that will be developed by Multiline Design. This research applies the Analytic Hierarchy Process (AHP) method because it has a clear decision hierarchy structure, a systematic analysis step guide and special measures to evaluate the level of consistency of the assessment. This research evaluates three alternative furniture craftsmen/workshops using eight criteria. Data for evaluation comes from observations and interviews with alternative craftsmen/furniture workshops and internal Multiline parties. The analysis results show that the ability to produce according to design is the most important criterion. The results of the analysis also concluded that the furniture craftsman/workshop with the pseudonym code